2018
DOI: 10.1371/journal.pone.0195050
|View full text |Cite
|
Sign up to set email alerts
|

A high content, high throughput cellular thermal stability assay for measuring drug-target engagement in living cells

Abstract: Determining and understanding drug target engagement is critical for drug discovery. This can be challenging within living cells as selective readouts are often unavailable. Here we describe a novel method for measuring target engagement in living cells based on the principle of altered protein thermal stabilization / destabilization in response to ligand binding. This assay (HCIF-CETSA) utilizes high content, high throughput single cell immunofluorescent detection to determine target protein levels following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Starting from cells in suspension, after drug treatment and subsequent CETSA heating in PCR-tubes, cells were washed and collected by centrifugation before being transferred to clear bottom plates where they were fixed and stained (anti-tubulin and Hoechst). After we had developed this CETSA imaging format, two articles describing related methods were published on CETSA drug screening on adherent cells, demonstrating the feasibility of the image-based detection of target engagement 29,30 . Our method is, however, more versatile and allows for studies of clinical samples of cell suspensions such as fine needle aspirates.…”
Section: Resultsmentioning
confidence: 99%
“…Starting from cells in suspension, after drug treatment and subsequent CETSA heating in PCR-tubes, cells were washed and collected by centrifugation before being transferred to clear bottom plates where they were fixed and stained (anti-tubulin and Hoechst). After we had developed this CETSA imaging format, two articles describing related methods were published on CETSA drug screening on adherent cells, demonstrating the feasibility of the image-based detection of target engagement 29,30 . Our method is, however, more versatile and allows for studies of clinical samples of cell suspensions such as fine needle aspirates.…”
Section: Resultsmentioning
confidence: 99%
“…CETSA HT would benefit greatly from endpoints allowing greater amplification of signal when quantifying low levels of endogenous thermostable protein, allowing a larger assay window and reducing requirements for cell numbers. Recent reports of identification of individual antibodies capable of selectively quantifying thermostable protein for p38α 10 and Chk1 11 have enabled application of CETSA with an imaging endpoint for these targets. This endpoint both allows single-cell resolution of target engagement and reduces requirements for cell numbers, though the successful application of this approach to measure binding to targets with low expression remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 While such assays can be constructed using tagged proteins overexpressed in cells, [7][8][9] assays that measure label-free target engagement with endogenous protein by high-throughput CETSA (CETSA HT) have only been reported for a handful of targets to date. 5,[10][11][12] These studies have demonstrated that this technology might be used for compound screening to identify hits that are able to access and engage the target of interest in live cells, and to determine a measure of apparent potency of intracellular binding to rank compounds and inform on structure-activity relationships (SARs). 5,9,13 Variations in the assay setup have also been shown to differentiate compounds based on the kinetics of intracellular target engagement.…”
Section: Introductionmentioning
confidence: 99%
“…The method quantifies “soluble” protein in adherent cells, as the antigenic epitope becomes inaccessible upon heating and aggregation. Massey reported such an assay, named HCIF-CETSA, 19 and demonstrated heat-dependent aggregation and loss of immunofluorescence for the serine/threonine protein kinase Chk1. Interestingly, treatment with the Chk1 inhibitor V158411 resulted in a more rapid loss of immunofluorescence upon heating, in contrast to thermal stabilization observed with this compound by traditional CETSA; 20 this discrepancy is not fully understood but highlights the potential for CETSA detection modalities to show discordant results.…”
Section: Introductionmentioning
confidence: 99%